UJI SENSITIVITAS MYCOBACTERIUM TUBERCULOSIS TERHADAP OBAT ANTI TUBERKULOSIS PADA PENDERITA TUBERKULOSIS PARU DENGAN DIABETES MELITUS - Yuniarti, Elsa (Sainstek : Jurnal Sains dan Teknologi, 2015)
Diabetes mellitus is a chronic disease marked with high blood sugar levels. Patients with diabetes mellitus susceptible to pulmonary tuberculosismaking it difficult for to cure them. This research aims to find out figure of anti tuberculosis drug resistance in patients with pulmonary tuberculosis with diabetes mellitus. This descriptive research was conducted in the Laboratory of Microbiology Center for Lung Disease Treatment Lubuk Alung West Sumatra. Sputum samples were pulmonary tuberculosis patients with diabetes mellitus as many as 10 samples. The results of Mycobacterium tuberculosis sensitivity to anti-tuberculosis drugs in patients with pulmonary tuberculosis with diabetes mellitus showed resistance to one drug, isoniazid by 10% and the other anti tuberculosis drugs are not resistance.Key words : diabetes mellitus, pulmonary tuberculosis, anti tuberculosis drugs, resistance